Segregated Cell Populations Enable Distinct Parallel Encoding within the Radial Axis of the CA1 Pyramidal Layer - Geiller, Tristan; Royer, Sebastien; Choi, June-Seek (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2017)
Numerous studies have implicated the hippocampus in the encoding and storage of declarative and spatial memories. Several models have considered the hippocampus and its distinct subfields to contain homogeneous pyramidal cell populations. Yet, recent studies have led to a consensus that the dorso-ventral and proximo-distal axes have different connectivities and physiologies. The remaining deep-superficial axis of the pyramidal layer, however, remains relatively unexplored due to a lack of techniques that can record from neurons simultaneously at different depths. Recent advances in transgenic mice, two-photon imaging and dense multisite recording have revealed extensive disparities between the pyramidal cells located in the deep and the superficial layers. Here, we summarize differences between the two populations in terms of gene expression and connectivity with other intra-hippocampal subregions and local interneurons that underlie distinct learning processes and spatial representations. A unified picture will emerge to describe how such local segregations can increase the capacity of the hippocampus to compute and process numerous tasks in parallel.
Keywords: PLACE CELLS; CANNABINOID RECEPTORS; HIPPOCAMPAL-FORMATION; SPATIAL NAVIGATION; FUNCTIONAL DOMAINS; DENTATE GYRUS; MEMORY; RAT; DYNAMICS; AREA